Freehand vs. computer-aided implant surgery: a systematic review and meta-analysis—part 1: accuracy of planned and placed implant position - Joscha G. Werny; Katharina Frank; Shengchi Fan; Keyvan Sagheb; Bilal Al-Nawas; Clement T. Narh; Eik Schiegnitz (International Journal of Implant Dentistry)
Abstract Objectives This systematic review aimed to investigate and compare the accuracy of free-hand and computer-aided implant surgery (CAIS) approaches in dental implant placement. Material and methods The PICO question as follows: In patients receiving dental implants, does computer-aided implant surgery superior in accuracy compared to non-computer-aided implant surgery? The primary outcome was angular deviation between the planned and placed position of the implant. An electronic search was made to identify all relevant studies reporting the accuracy of CAIS approaches and freehand for dental implant placement. The data were extracted in the descriptive description, and a meta-analysis of single means was performed to estimate the deviations for each variable using a random-effects model. Results Out of 1609 initial articles, 55 were selected for data extraction. The mean value of angular, entry, and apex deviations were 7.46°, 1.56 mm, and 2.22 mm for freehand, 5.94°, 1.13 mm, and 1.43 mm for pilot drill-sCAIS, 2.57°, 0.72 mm, 0.88 mm for fully guided-sCAIS (fg-sCAIS), and 3.67°, 1.01 mm, and 1.36 for dynamic CAIS (dCAIS), respectively. Significant differences were found between the freehand and CAIS approaches (p < 0.04). Fg-sCAIS was significantly more accurate than dCAIS systems at the entry (p < 0.001). Conclusions Compared to the freehand approach, both sCAIS and dCAIS improve implant placement accuracy, with angular deviations ranging from 2° to 6°. Detailed planning is crucial for CAIS, particularly for fg-sCAIS, which demonstrated the highest accuracy than others. As apex deviations of 1 to 2 mm have been observed in CAIS approaches, a 2-mm safety margin should be implemented to minimize surgical risks.